Answer:
2√6
Step-by-step explanation:
find the hypotenuse of the triangle thats 3 and 7
pythagorean
3 squared + 7 squared
16 + 49 = 57
√57 is the hypotenuse
√57 is also the base of the triangle that has side thats 9
pythagorean theorem
x squared + √57 squared = 9 squared
x^2 + 57 = 81
x^2 = 81 - 57
x^2 = 24
x = √24
x = √4 * √6
x = 2√6
Answer:
The unit price is $0.90.
Step-by-step explanation:
$2.71 divided by 3 = 0.9033333333333.
Rounded equals: $0.90.
Answer:
Your final answer is either
x≥-2 if your initial inequality was
6x+2≤2(5-x)
OR
x≤-2
if your initial inequality was
6x+2≥2(x-2)
Step-by-step explanation:
As shown you have an equality, not an inequality.
-6x+2=2(5-x) distribute through parenthesis
-6x+2=2(5)+2(-x)
-6x+2=10-2x add 2x to both sides
2x-6x+2=10-2x+2x
-4x+2=10 subtract 2 from both sides
-4x+2-2=10-2
-4x=8 divide both sides by -4
-4x/(-4) = 8/(-4)
x = -2
With the ≥ or ≤ sign you would solve the exact same way
except for the point where when dividing both sides by
-4 requires you to reverse the inequality.
Your final answer is either
x≥-2 if your initial inequality was
6x+2≤2(5-x)
OR
x≤-2
if your initial inequality was
6x+2≥2(x-2)
Answer: I think the answer is n=2
Step-by-step explanation: